Faktor-Faktor yang Mempengaruhi Penurunan Jumlah Mahasiswa Matematika di Universitas PGRI Wiranegara - Lutfiah, Ainul; Supriyo (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to identify internal and external factors that influence the decline in the number of students in the Mathematics Education Study Program at PGRI Wiranegara University (UNIWARA). This study uses a quantitative approach with descriptive statistical analysis. The research subjects were all active students of the Mathematics Education Study Program at UNIWARA from the 2022–2024 cohorts, totaling 54 students, using total sampling techniques. Data were collected through Likert scale questionnaires, observations, and documentation, then analyzed using descriptive statistics through the calculation of mean values and percentages. The results showed that internally, the pedagogical quality of lecturers was in the fairly good category, but there were still weaknesses in academic management and supporting facilities, especially the stability of the lecture schedule and campus internet access. External factors included competition with other universities, more active and attractive promotional strategies, and consideration of tuition fees. Therefore, the decline in student enrollment is influenced by a combination of internal and external factors that require efforts to improve academic services and strengthen promotional strategies on an ongoing basis.